GILT - A randomised phase III study of oral vinorelbine and cisplatin with concomitant radiotherapy followed by either consolidation therapy with oral vinorelbine and cisplatin or best supportive care alone in stage III non-small cell lung cancer - Flentje, Michael; Huber, Rudolf M.; Engel-Riedel, Walburga; Andreas, Stefan; Kollmeier, Jens; Staar, Susanne; Dickgreber, Nicolas; Vaissiere, Nathalie; De Almeida, Cecilia; Edlich, Birgit; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
Concurrent chemoradiotherapy (CRT) is considered standard for inoperable stage III non-small cell lung cancer (NSCLC). Consolidation chemotherapy (CC) following CRT is intended to further improve outcomes, yet studies have shown discordant results. This phase III study assessed CRT followed by best supportive care (BSC) or consolidation with oral vinorelbine and cisplatin.Patients received two cycles of oral vinorelbine (50 mg/m(2) days 1, 8 and 15) + cisplatin (20 mg/m(2) days 1-4) q4w + radiotherapy (RT; 66 Gy). Patients with at least stable disease (SD) were randomised to either two cycles oral vinorelbine (60-80 mg/m(2) days 1 and 8) + cisplatin (80 mg/m(2) day 1) q3w + BSC or BSC alone. Primary endpoint was progression-free survival (PFS).A total of 279 patients were enrolled for CRT and 201 patients were randomised to CC or BSC. Both CRT and CC were well tolerated, with limited radiation-mediated grade 3/4 toxicities (CRT/CC/BSC: oesophagitis-related events 12.9 %/3.1 %/0 %; grade 3 pneumonitis 0 %/0 %/2 %) and chemotherapy-mediated grade 3/4 toxicities (CRT/CC: neutropenia 11.2 %/22.1 %; leukopenia 18.3 %/26.7 %; grade 3 nausea 5.0 %/2.3 %, grade 3 vomiting 3.2 %/3.5 %). Median PFS from randomisation was 6.4 (5.0-8.7) and 5.5 (3.8-7.4) months in the CC and BSC arms (hazard ratio, HR = 0.93 [0.69-1.26]; p = 0.63), respectively; median overall survival (OS) 20.8 (13.5-25.3) and 18.5 (13.6-24.7) months, respectively.Consolidation chemotherapy after concurrent CRT did not prolong PFS or OS. Concurrent RT with oral vinorelbine and cisplatin demonstrated a favourable safety profile and represents a suitable treatment regimen for inoperable stage III NSCLC.
EVALuna2:18353